1997
DOI: 10.1038/bjc.1997.314
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of metastatic renal cell carcinoma with subcutaneous interleukin 2: evidence for non-renal clearance of cytokines

Abstract: Summary The circulating cytokine concentrations following administration of subcutaneous recombinant interleukin 2 (IL-2) in combination with interferon a and 5-fluorouracil used to treat advanced renal cancer were studied. One patient was anephric and on dialysis, and seven had normal biochemical renal function, although five had undergone single nephrectomy. The pharmacokinetics of IL-2 and changes in IL-6 and tumour necrosis factor (TNF)-a were essentially similar in all patients including the anephric pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…For IL-6, up to 80% may be cleared by the rat liver [ 132 ]. In humans on dialysis, the pharmacokinetics of low dose IL-2 and changes in IL-6 and TNF-α were essentially similar in all patients studied, including one anephric patient, irrespective of the periods of dialysis [ 133 ]. However, higher doses of IL-2 may have renal clearance and this was attributed to saturation of physiological clearance mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For IL-6, up to 80% may be cleared by the rat liver [ 132 ]. In humans on dialysis, the pharmacokinetics of low dose IL-2 and changes in IL-6 and TNF-α were essentially similar in all patients studied, including one anephric patient, irrespective of the periods of dialysis [ 133 ]. However, higher doses of IL-2 may have renal clearance and this was attributed to saturation of physiological clearance mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Banks et al. (7), who also administered subcutaneous injections of IL‐2 at low doses to anephric hemodialysis patients, suggested the possibility of non‐renal clearance of IL‐2 and reported that IL‐2 could be used safely in these patients. In the present study, we measured serum concentrations of IL‐2 and calculated pharmacokinetic parameters of IL‐2 to determine whether intravenous injection of low‐dose IL‐2 is possible and safe in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in patients with impairment of renal function, IL‐2 may cause serious adverse reactions. Although there have been some reports on its pharmacokinetics after subcutaneous injection (6,7), few reports have been published concerning the pharmacokinetics of IL‐2 administered intravenously to hemodialysis patients. We therefore determined the changes in blood concentration of IL‐2 following intravenous injection in hemodialysis patients and compared the results obtained with those in non‐hemodialysis patients to assess the safety of intravenous IL‐2 injection in patients undergoing hemodialysis.…”
mentioning
confidence: 99%